Degradation rates of various earthing conductors in different soil environments - Hamzah, Muhammad Noh; Ab Kadir, Mohd Zainal Abidin; Sobri, Shafreeza; Gomes, Chandima; Abdul Raof, Nurliyana (Universiti Putra Malaysia Press, 2026)
The study evaluates the degradation of electrical earthing conductors that are commonly used in electrical earthing. Electrical earthing equipment is exposed to various environments that causes it to corrode and obstruct the proper function of the electrical protection system of any structure. There have been numerous reports of integrity loss of the electrical protection system encased in soil. The aim of this study is to explore the most durable metal when encased in native and aggressive soil conditions and corrosion protection techniques through sealing. Earthing electrodes samples are encased in the soil for 3 months to evaluate their corrosion rates. Aluminium was seen to have the best performance of withstanding corrosion at 0.1792 mpy (mpy stands for mils per year) and 0.0758 mpy when partially immersed in soil vertically without seal in bentonite and native soil respectively. Copper bonded steel when fully immersed horizontally, was shown to have the least effective performance at values of 0.9960 mpy and 1.6101 mpy in bentonite and native soil individually. Copper showed high corrosion rates of 0.3917 mpy when immersed in bentonite when it is partially air sealed. Partial sealing of metals samples shows significant corrosion rate reduction up to 91.41 %. Visual observations show various corrosion product formations to the metals. These findings highlight the importance of selecting the best materials for earthing to secure the most efficient metals against corrosion and the mitigation methods to sustain electrical earthing systems in the long term.